2022
DOI: 10.3390/jsan11040065
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy-Logic Based Adaptive Data Rate Scheme for Energy-Efficient LoRaWAN Communication

Abstract: Long Range Wide Area Network (LoRaWAN) technology is rapidly expanding as a technology with long distance connectivity, low power consumption, low data rates and a large number of end devices (EDs) that connect to the Internet of Things (IoT) network. Due to the heterogeneity of several applications with varying Quality of Service (QoS) requirements, energy is expended as the EDs communicate with applications. The LoRaWAN Adaptive Data Rate (ADR) manages the resource allocation to optimize energy efficiency. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The research was focused on using the Xingyun satellite services using patented satellite transceiver names such as LEOBIT. Meanwhile, Rachel et al [11] suggested an ADR algorithm based on fuzzy logic for LoRaWAN gateway systems. Even though that research demonstrated superior performance in terms of energy consumption and transmission power compared to the Semtech ADR scheme, it showed that the Semtech ADR scheme is ideal in terms of energy consumption.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The research was focused on using the Xingyun satellite services using patented satellite transceiver names such as LEOBIT. Meanwhile, Rachel et al [11] suggested an ADR algorithm based on fuzzy logic for LoRaWAN gateway systems. Even though that research demonstrated superior performance in terms of energy consumption and transmission power compared to the Semtech ADR scheme, it showed that the Semtech ADR scheme is ideal in terms of energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…In Figure 3, the spherical triangle is redrawn to compute central angle γ subtended by circle arc ES, and the law of cosines is applied to the sides as shown in Equations ( 10) and (11).…”
Section: 𝑡𝑎𝑛𝜃 = 𝑧 𝑥 + 𝑦 (8)mentioning
confidence: 99%
See 1 more Smart Citation
“…Kufakunesu et al [23] designed a TPC based on a Mandami Fuzzy Interference System that runs in the NS and infers the transmission parameters based on the historical data of the SNR. They reduced the size of the historical SNR data from 20 samples (traditional ADR) to four samples, improving the convergence time.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recently in [ 12 ], the authors extend their previous work [ 8 ] applying a variable-order hidden Markov model to predict the ED mobility pattern in the case of “unknown or undefined trajectories”. Eventually, the recent paper [ 13 ] in Table 1 presents a survey of different ADR algorithms that appeared in the literature.…”
Section: Introductionmentioning
confidence: 99%